PENGARUH MACROECONOMIC DAN BANK SPECIFIC FACTORS TERHADAP PROFITABILITAS PERBANKAN KONVENSIONAL YANG TERDAFTAR DI BEI - Juansa Piter Parulian; Susy Muchtar (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
Banking as one of the economic sub-systems that supports the progress of the nation. As financial institutions, banks are authorized to manage money by accepting deposits, providing loans and investments. In order to avoid liquidity problems and even the possibility of business bankruptcy at a bank that can be detected from the start, a profitability analysis is needed. Based on the identification of the problem, this study aims to influence internal banking factors as measured by asset size, deposits, liquidity risk, GDP and inflation on profitability as measured through return on assets in 29 conventional banks listed on the Indonesia Stock Exchange for 6 years (2015-2020) . The data used is obtained from financial reports and annual banking reports on the IDX, Bank Indonesia websites, OJK, BPS, and the official website of each conventional bank for the 2017-2021 period. The research data testing method uses panel data regression which is divided into 3 models, namely common effect, fixed effect, and random effect. Based on the analysis it can be concluded that asset size, deposits, liquidity risk, GDP and inflation have a significant effect on profitability